In Vivo Dosimetry in Radiotherapy: Techniques, Applications, and Future Directions - James C. L. Chow; Harry E. Ruda (Encyclopedia)
In vivo dosimetry (IVD) is a vital component of modern radiotherapy, ensuring accurate and safe delivery of radiation doses to patients by measuring dose parameters during treatment. This paper provides a comprehensive overview of IVD, covering its fundamental principles, historical development, and the technologies used in clinical practice. Key techniques, including thermoluminescent dosimeters (TLDs), optically stimulated luminescent dosimeters (OSLDs), diodes, metal-oxide-semiconductor field-effect transistors (MOSFETs), and electronic portal imaging devices (EPIDs), are discussed, highlighting their clinical applications, advantages, and limitations. The role of IVD in external beam radiotherapy, brachytherapy, and pediatric treatments is emphasized, particularly its contributions to quality assurance, treatment validation, and error mitigation. Challenges such as measurement uncertainties, technical constraints, and integration into clinical workflows are explored, along with potential solutions and emerging innovations. The paper also addresses future perspectives, including advancements in artificial intelligence, adaptive radiotherapy, and personalized dosimetry systems. This entry underscores the critical role of IVD in enhancing the precision and reliability of radiotherapy, advocating for ongoing research and technological development.